2022
DOI: 10.1155/2022/3660110
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a Novel Risk Model: A Five-Gene Prognostic Signature for Pancreatic Cancer

Abstract: Objective. Biomarkers for pancreatic cancer (PCa) prognosis provide evidence for improving the survival outcome of this disease. This study aimed to identify a prognostic risk model based on gene expression profiling of microarray bioinformatics analysis. Methods. Prognostic immune genes in the TCGA-PAAD cohort were identified using the univariate Cox regression and Kaplan–Meier survival analysis. Multivariate Cox regression (stepAIC) was used to identify prognostic genes from the top 20 hub genes in the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…A number of studies had proposed potential roles of these NKGs in PC. For instance, the tumor necrosis factor ligand superfamily member 10 (TNFSF10), also known as TRAIL, encodes a cytokine that belongs to the tumor necrosis factor (TNF) ligand family, it preferentially induces apoptosis in transformed and tumor cells and was proposed as a prognostic indicator of PC ( Wang et al, 2021 ; Wang et al, 2022 ). As a well-known driver gene, KRAS frequently mutated in PC patients ( Waters and Der, 2018 ), our data revealed that KRAS was the most mutated gene in the TCGA-PAAD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies had proposed potential roles of these NKGs in PC. For instance, the tumor necrosis factor ligand superfamily member 10 (TNFSF10), also known as TRAIL, encodes a cytokine that belongs to the tumor necrosis factor (TNF) ligand family, it preferentially induces apoptosis in transformed and tumor cells and was proposed as a prognostic indicator of PC ( Wang et al, 2021 ; Wang et al, 2022 ). As a well-known driver gene, KRAS frequently mutated in PC patients ( Waters and Der, 2018 ), our data revealed that KRAS was the most mutated gene in the TCGA-PAAD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%